A competitive reverse transcription: PCR to study apolipoprotein ε gene expression - Rexin, Martin; Feussner, Giso (Clinical chemistry, 1998)
We developed a rapid and simple competitive reverse transcription-polymerase chain reaction for the quantification of apoε mRNA in human monocyte-derived macrophages. The method was applied, and its reliability was shown in patients with the familial lipoprotein disorder, type III hyperlipoproteinemia. Type III hyperlipoproteinemic patients express markedly higher concentrations of apoε mRNA when compared with healthy controls. Patients with this disease are usually (>90%) homozygous for a receptor binding-defective isoform of apolipoprotein apo E (apo E2). The higher expression of apoε mRNA in the patients could, therefore, be a physiological mechanism to compensate for functionally defective apo E. The developed procedure might be valuable in assessment of apoε gene expression in human disease.